A Novel Approach to Improve Inventory Management Process of Pharmaceutical Supply Chain - Wang, Chia-Nan; Nguyen, Thuy-Duong; Thieu Pham, Phuong-Nhi; Do, Ngoc-Hien (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The pharmaceutical industry relies heavily on efficient inventory management to guarantee the expeditious supply of medications, minimize wastage, and sustain cost control. The dynamic demand for pharmaceuticals and severe regulatory standards present unique inventory management challenges that require systematic and strategic approaches. In Vietnam, a market undergoing accelerated development, the pharmaceutical company must also ensure that its supply chain and inventory administration are efficient. The ineffective operation of the pharmaceutical company’s facility is identified as a problem requiring improvement in this study. By employing statistical data analysis and root cause analysis techniques, the researchers ascertained that an overburdened inventory level is the underlying cause of the inefficiency in the warehouse. Hence, to relieve the pressure on the organization’s warehouse, this study suggests the implementation of a buffer warehouse through the utilization of an innovative integrated Lean Six Sigma approach—DMADV (Define, Measure, Analyze, Design, Verify)—and Multi-criteria decision-making (MCDM) methodology. The design process begins with identifying and analyzing stakeholder requirements and constraints. This is followed by creating Risk Priority Numbers (RPN) and Ishikawa diagrams, which serve as capability indicators for the buffer warehouse. Utilizing the Best-Worst Method (BWM) and the Evaluation Based on Distance from the Average Solution (EDAS) with a Z-number, the study develops a buffer warehouse supplier selection that is optimal for the organization’s supply chain. In conclusion, the research outlines a strategy and a collection of metrics for assessing the efficiency of the buffer warehouse operation. The application of DMADV for analyzing problem-solving is investigated, and a buffer warehouse for inventory is established. Furthermore, the research results provide metrics for buffer warehouse capacity, a methodology for choosing buffer warehouses, and a framework for assessing their efficacy. This results in approximately USD 25,523 in savings or 30 fewer late orders.